PELAKSANAAN PROGRAM PENGUATAN PENDIDIKAN KARAKTER (PPK) BERBASIS KELAS MELALUI MANAJEMEN KELAS DI SEKOLAH DASAR - Dalia Rosita Ria Yulian; Santhy Hawanti; Okto Wijayanti (JURNAL TEMATIK, 2019)
This study aims to describe; 1). Strengthening Educational Character Program (PPK) based on classroom management in elementary school, 2). The obstacles on the implementation of Strengthening Educational Character Program (PPK) based on classroom management, 3). The solutions of the implementation of Strengthening Educational Character Program (PPK) based on classroom management. This research belonged to descriptive qualitative. The researcher used interview, observation, and documentation as the technique of collecting data. The result of this research showed that: 1). Strengthening Educational Character Program (PPK) based on classroom management had done through class dealing, class control, and classroom settings by integrating character values, 2). The obstacles in the implementation of Strengthening Educational Character Program (PPK) based on classroom management was the willingness of students to obey the lack of classroom agreements and the limitations of classrooms, 3). The solution of the problems were teachers should give counselling, to hold meeting, and minimized the tools and media within the classroom.